2022
DOI: 10.3390/atmos13091471
|View full text |Cite
|
Sign up to set email alerts
|

A Multi Criteria Decision Analysis Approach for Regional Climate Model Selection and Future Climate Assessment in the Mono River Basin, Benin and Togo

Abstract: Regional climate models (RCMs) are key in the current context of global warming, and they are increasingly used to support decision-making and to identify adaptation measures in response to climate change. However, considering the wide range of available RCMs, it is important to identify the most suitable ones prior to climate impact studies, especially at small scales like catchments. In this study, a multicriteria decision analysis approach, namely the technique for order preferences by similarity to an idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…This all‐encompassing analysis gives a more solid and well‐rounded appraisal of GCMs. Multiple studies have confirmed the usefulness of selecting GCMs based on some criteria (Ahmadalipour et al, 2015; Hounguè et al, 2022; M. J. U. Khan et al, 2020; McSweeney et al, 2014; Salehie, Hamed et al, 2022; Shiru et al, 2019). The studies indicated that the rigour, transparency, and efficiency of GCM selection for climate change research improves using criteria‐based GCM selection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This all‐encompassing analysis gives a more solid and well‐rounded appraisal of GCMs. Multiple studies have confirmed the usefulness of selecting GCMs based on some criteria (Ahmadalipour et al, 2015; Hounguè et al, 2022; M. J. U. Khan et al, 2020; McSweeney et al, 2014; Salehie, Hamed et al, 2022; Shiru et al, 2019). The studies indicated that the rigour, transparency, and efficiency of GCM selection for climate change research improves using criteria‐based GCM selection.…”
Section: Discussionmentioning
confidence: 96%
“…This all-encompassing analysis gives a more solid and well-rounded appraisal of GCMs. Multiple studies have confirmed the usefulness of selecting GCMs based on some criteria (Ahmadalipour et al, 2015;Hounguè et al, 2022; M. J. U. Khan et al, 2020;McSweeney et al, 2014;Shiru et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, poverty, the proximity of farms and settlements to the river, and the lack of early warning systems were identified as the main vulnerability drivers in the LMR basin [42,43]. Moreover, recent studies based on climate and land use change scenarios in the catchment reported a potential intensification of rainfall and more frequent extreme flood events by 2050 [44,45]. In that regard, the two countries are planning a second dam, the Adjarala Dam, which is intended, among other goals, to reduce extreme flood impacts downstream.…”
Section: Case Studymentioning
confidence: 99%
“…Supporting the discussions and engagement of stakeholders, numerous tools and products were used to communicate flood hazards, scenarios of return periods as well as climate and land use change [44,46]. For spatio-temporal products on flood hazard base cases and scenarios, the Telemac-2D and Soil Water and Assessment Tool (SWAT) were used as the hydrodynamic and hydrological models, respectively.…”
Section: Transboundary Collaborative Modeling Lmr Frameworkmentioning
confidence: 99%
“…Different studies have attempted to evaluate the ability of the CMIP5 GCMs and CORDEX Africa RCMs in simulating precipitation and temperature at the global scale [ 2 , 9 , 10 , 13 , 14 , 17 , 21 , 22 , 24 , 26 , 28 , 30 ], regional scale [ 23 , 29 , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], and sub-regional (national) scale [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. So far, the multimodel ensembles of the CMIP5 GCMs for the projection of climate variables have been effectively used [ 47 ], and some authors have confirmed the superiority of these ensembles over individual GCMs [ 48 ].…”
Section: Introductionmentioning
confidence: 99%